Interdisciplinary Humanities through Islamic Epistemology: Rethinking Japanese Curriculum Reform - Habib Badawi (TATHO: International Journal of Islamic Thought and Sciences, 2026)
This study aims to reconstruct and reinterpret the reform of the interdisciplinary humanities curriculum in Japan through the perspective of Islamic thought and science. Rather than positioning Japanese educational reform as a secular model that stands alone, this study places it as a comparative mirror to reexamine the principles of Islamic epistemology, particularly the concepts of the unity of knowledge (tawḥīd al-ʿilm), the integration of revelation and reason (naql–ʿaql), and the orientation of education based on maqāṣid al-sharīʿah. This study uses a qualitative-analytical and comparative approach by analysing curriculum documents, previous empirical findings, and classical and contemporary Islamic thought. The results of the analysis show that the reform of the Japanese humanities curriculum implicitly reflects values that are in line with the Islamic intellectual tradition, such as the rejection of the fragmentation of knowledge, the affirmation of the ethical dimension in learning, the strengthening of cultural-global awareness, and transformative learning that shapes the perspectives and social responsibilities of students. These findings confirm that the integration of the humanities is not a foreign concept in Islam, but rather has strong epistemological roots in the Islamic scientific tradition